Language Learning in Study Abroad: Social, Cultural, and Identity-Related Factors: Erasmus Students in Northern, Southern, and Eastern-European English as a Lingua Franca Contexts (2023)
Study abroad has been a matter of concern in sociolinguistics for a few decades now. Nevertheless, research on study abroad has rarely combined the study of sociolinguistic aspects with the analysis of perceived language-related gains. Similarly, there has been a lack of studies integrating qualitative and quantitative methods in SA research. Thus, the present volume comes as a response to the need to triangulate sociolinguistic aspects with perceived language-related gains, qualitative and quantitative methods, in three different European contexts, and participants from almost every corner in Europe for a deeper understanding of the study abroad phenomenon on the European continent.La realització d’estudis a l’estranger ha estat motiu d’interès per a la sociolingüística des de fa algunes dècades. Tanmateix, la investigació sobre aquest tema rares vegades ha combinat l’estudi dels aspectes sociolingüístics amb l’anàlisi dels assoliments percebuts relacionats amb l’idioma. De manera semblant, manquen treballs que integren els mètodes qualitatius amb els quantitatius en l’anàlisi sociolingüística. Així, aquest volum sorgeix com a resposta a la necessitat de relacionar els aspectes sociolingüístics amb guanys percebuts relacionats amb el llenguatge, els mètodes qualitatius i els quantitatius, en tres contextos europeus diferents i amb participants de quasi tots els racons d’Europa per a una comprensió més profunda del fenomen dels estudis a l’estranger en el continent europeu.
Keywords: study abroad; language learning; determinants for language learning in study abroad